Method for testing diffusion coefficient of positive electrode material and method for evaluating structural stability of positive electrode material
By testing the diffusion coefficient of the cathode material of lithium-ion battery under infinitely small excitation current, the cumbersome test process in the prior art is solved, and the structural stability of the cathode material is achieved quickly and accurately evaluated, reducing the development cycle and cost.
Patent Information
- Application Number
- CN202411354762.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-07
AI Technical Summary
The prior art When evaluating the structural stability of the cathode material of lithium-ion batteries, the testing process is cumbersome and time-consuming, resulting in a prolonged development cycle and the inability to quickly and accurately determine the cause of capacity attenuation.
By testing the diffusion coefficient of the positive electrode material under an infinitely small excitation current, using multiple excitation-stasis processes, the relationship between K1 and excitation current I is calculated, and the diffusion coefficient D of the positive electrode material is calculated, and the diffusion coefficient D is calculated according to the diffusion coefficient and the number of cycles is circulated according to the diffusion coefficient. The change curve evaluates structural stability.
The rapid and accurate evaluation of the structural stability of the positive electrode material is achieved, avoiding the influence of changes in the surface ion concentration of the positive electrode material during the excitation process, and reducing the testing time and cost.
Smart Images

Figure CN119269339A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a method for testing the diffusion coefficient of a positive electrode material and a method for evaluating the structural stability. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, long cycle life, low self-discharge rate and light weight, so they are widely used in mobile devices, electric vehicles, energy storage systems and other fields. As a secondary battery, lithium batteries will experience capacity decay due to factors such as active lithium loss, positive electrode material structural damage and current collector corrosion during long-term cycles. Therefore, accurately determining the cause of capacity decay will help to propose targeted measures to improve capacity decay. Among them, accurately evaluating (assessing) the structural stability of positive electrode materials during long cycles has become a research focus in the field.
[0003] At present, the main method is to assemble positive electrode materials into batteries, conduct cycle performance tests on the batteries, obtain the capacity retention rate of the battery's maximum cycle number, and conduct relevant physical and chemical characterization of the positive electrode materials or perform power-off and reassembly to determine whether the structure of the positive electrode materials is lost. However, in general, obtaining the capacity of the battery's maximum cycle number and conducting post-cycle structural loss test analysis will take a lot of time, resulting in a long development cycle for positive electrode materials, which in turn causes a lot of manpower and material resources to be consumed.
[0004] Evaluating the structural stability of positive electrode materials during long cycles from the perspective of the diffusion coefficient of positive electrode materials has a high research value, which depends on how to accurately test the diffusion coefficient of positive electrode materials. Therefore, how to quickly test the diffusion coefficient of positive electrode materials to evaluate the structural stability of positive electrode materials has become a research focus in the field. Summary of the invention
[0005] The present invention provides a method for testing the diffusion coefficient of a cathode material and a method for evaluating the structural stability, which can accurately calculate the diffusion coefficient of the cathode material under an infinitesimal excitation current and quickly evaluate the structural stability of the cathode material.
[0006] The present invention provides a method for testing the diffusion coefficient of a positive electrode material, comprising the following steps: (1-1) assembling a positive electrode sheet containing a positive electrode material into a first battery; (1-2) setting the charge state of the first battery to 10% to 90% SOC to obtain a first battery to be stimulated; (1-3) sequentially using different stimulation currents I to perform multiple stimulation-resting processes on the first battery to be stimulated to obtain K1 corresponding to different stimulation currents I; wherein, among the multiple stimulation-resting processes, the K1 corresponding to the nth stimulation-resting process is calculated according to the following formula 1:
[0007]
[0008] Wherein, ΔEs is the voltage difference between the first battery to be stimulated and the battery after the x-th stimulation-resting process; ΔEt is the voltage difference between the first battery to be stimulated and the battery after the stimulation during the x-th stimulation-resting process;
[0009] (1-4) obtaining the relationship between K1 and the excitation current I according to K1 corresponding to the different excitation currents I, and obtaining the K1 corresponding to the excitation current I=0 according to the relationship between K1 and the excitation current I;
[0010] Substitute the K1 corresponding to the excitation current I=0 into Formula 2 to calculate the diffusion coefficient D of the positive electrode material:
[0011]
[0012] Wherein, π is the circumference of a circle; t is the excitation time of the excitation in each excitation-resting process, in seconds; m a is the mass of the positive electrode material in the positive electrode sheet, in grams; V M is the molar volume of the positive electrode material in the positive electrode sheet, in cm 3 ; S is the active contact surface area between the positive electrode material in the positive electrode sheet and the first battery electrolyte, in cm 2 ;M B is the molar mass of the positive electrode active material, in g / mol.
[0013] Optionally, in the multiple excitation-rest processes, the excitation current I during the excitation in each excitation-rest process is independently 0.01C to 0.5C; and / or, in any two adjacent excitation-rest processes, the difference in the excitation current during the excitation is 0.02C to 0.1C; and / or, the excitation current used in the multiple excitation-rest processes increases sequentially.
[0014] Optionally, the excitation time t in each excitation-resting process is 100s to 1200s; and / or the resting time in each excitation-resting process is 0.5h to 2h.
[0015] Optionally, the process of making the charge state of the first battery 10% to 90% SOC to obtain the first battery to be stimulated includes: charging the first battery with constant current and constant voltage at a rate of 0.1C to the charge state of 10% to 90% SOC to obtain the first battery to be stimulated.
[0016] Optionally, the positive electrode sheet includes a positive electrode collector and a positive electrode active layer located on at least one side surface of the positive electrode collector, the positive electrode active layer includes the positive electrode material, a conductive agent and a binder, and in the positive electrode active layer, the mass percentage of the positive electrode material is 80% to 95%, the mass percentage of the conductive agent is 1% to 10%, and the mass percentage of the binder is 1% to 10%; and / or, the first battery also includes a negative electrode sheet, and the negative electrode sheet includes a lithium sheet; and / or, the first battery is a button battery.
[0017] The present invention also provides a method for evaluating the structural stability of a positive electrode material, comprising the following steps: (2-1) dividing a positive electrode material into N portions, and making each portion of the positive electrode material into a positive electrode sheet to obtain N positive electrode sheets; wherein N is an integer greater than or equal to 2; (2-2) assembling the N positive electrode sheets into N second batteries; (2-3) cycling y1 second batteries among the N second batteries with the same cycle system to obtain second batteries after y1 cycles; wherein the number of cycles i of the cycle of every two of the y1 second batteries is different; wherein y1 is an integer less than or equal to N; (2-4) respectively cycling the y1 second batteries after the y1 cycles Each of the second batteries is subjected to the following treatment to obtain the diffusion coefficient D of the positive electrode material in each of the second batteries after the cycle, thereby obtaining y1 diffusion coefficients D: (2-41) disassembling the second battery after the cycle and taking out the positive electrode sheet therefrom; (2-42) measuring the diffusion coefficient D of the positive electrode material in the positive electrode sheet according to the testing method for the diffusion coefficient of the positive electrode material according to any one of claims 1 to 5; (2-5) obtaining a variation curve of the diffusion coefficient D with the cycle number i based on the y1 diffusion coefficients D and their corresponding cycle numbers i; obtaining the slope k2 of the variation curve, -k2 / 10 -14 <1.2 The structural stability of the positive electrode material is better than -k2 / 10 -14 ≥1.2 corresponds to the structural stability of the positive electrode material.
[0018] Optionally, the number of cycles i of the cycles of the y1 second batteries is independently 50 to 1000.
[0019] Optionally, the cycle regime includes: charging the second battery at a first rate with a constant current to an upper limit of a material voltage, then charging at a constant voltage to a cutoff current of 0.01C to 0.1C, and then discharging the second battery at a second rate to a lower limit of a material voltage; wherein the first rate is 0.5C to 1C, and the second rate is 1C to 3C.
[0020] Optionally, the evaluation method also includes: in step (2-2), the diffusion coefficient D of y2 of the N second batteries is tested according to the testing method for the diffusion coefficient of the positive electrode material according to any one of claims 1 to 5, and is recorded as the initial diffusion coefficient D0; wherein y2 is an integer, and 1≤y2≤N-y1; the evaluating the structural stability of the positive electrode material according to the relationship between the diffusion coefficient D and the number of cycles i also includes: evaluating the structural stability of the positive electrode material according to D0, and the relationship between the diffusion coefficient D and the number of cycles i.
[0021] Optionally, the positive electrode sheet includes a positive electrode collector and a positive electrode active layer located on at least one side of the positive electrode collector, the positive electrode active layer includes the positive electrode material, a conductive agent and a binder, in the positive electrode active layer, the mass percentage of the positive electrode material is 80% to 95%, the mass percentage of the conductive agent is 1% to 10%, and the mass percentage of the binder is 1% to 10%; and / or, the second battery also includes a negative electrode sheet, the negative electrode sheet includes a negative electrode collector, and a negative electrode active layer located on at least one side of the negative electrode collector, the negative electrode active layer includes a negative electrode active material, a thickener, a conductive agent and a binder; wherein, in the negative electrode active layer, the mass percentage of the negative electrode active material is 90% to 96%, the mass percentage of the thickener is 1% to 5%, the mass percentage of the conductive agent is 1% to 2%, and the mass percentage of the binder is 1% to 3%; and / or, the negative electrode active material includes graphite.
[0022] The present invention provides a method for testing the diffusion coefficient of a positive electrode material and a method for evaluating the structural stability, which can accurately calculate the diffusion coefficient of the positive electrode material (such as the lithium ion diffusion coefficient) under an infinitesimal excitation current, avoid (eliminate) the influence of the concentration change of ions (such as lithium ions) on the surface of the positive electrode material during the excitation process, and quickly evaluate the structural stability of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a curve diagram showing the relationship between the excitation current and K1 in the battery before cycling in Example 1;
[0024] Figure 2 is a curve diagram showing the relationship between the excitation current and K1 in the battery after 50 cycles in Example 2;
[0025] Figure 3 This is a curve diagram showing the relationship between the excitation current and K1 in the battery after 300 cycles in Example 3. DETAILED DESCRIPTION
[0026] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0027] The embodiment of the present invention provides a method for testing the diffusion coefficient of a positive electrode material, comprising the following steps: (1-1) assembling a positive electrode sheet containing a positive electrode material into a first battery; (1-2) setting the charge state of the first battery to 10% to 90% SOC to obtain a first battery to be stimulated; (1-3) sequentially using different stimulation currents I to perform multiple stimulation-resting processes on the first battery to be stimulated to obtain K1 corresponding to different stimulation currents I; wherein, among the multiple stimulation-resting processes, the K1 corresponding to the nth stimulation-resting process is calculated according to the following formula 1:
[0028]
[0029] Where, ΔE s ΔE is the voltage difference between the first battery to be stimulated and the battery after the xth stimulation-resting process; t is the voltage difference before and after the stimulation of the first battery to be stimulated during the xth stimulation-resting process; (1-4) according to the K1 corresponding to different stimulation currents I, the relationship between K1 and the stimulation current I is obtained, and according to the relationship between K1 and the stimulation current I, the K1 corresponding to the stimulation current I=0 is obtained; the K1 corresponding to the stimulation current I=0 is substituted into formula 2 to calculate the diffusion coefficient D of the positive electrode material:
[0030]
[0031] Wherein, π is the circumference of a circle; t is the excitation time of each excitation-resting process, in seconds; m a V is the mass of the active substance of the positive electrode material in the positive electrode sheet, in grams; M is the molar volume of the positive electrode material in the active material positive electrode sheet, in cm 3 ; S is the active contact surface area between the positive electrode material in the positive electrode sheet and the electrolyte of the first battery, in cm; M B It is the molar mass of the active material of the positive electrode, in g / mol.
[0032] According to the inventor's research and analysis: the above-mentioned testing method for the diffusion coefficient of the positive electrode material (the positive electrode material to be evaluated or the positive electrode active material to be evaluated) can accurately calculate the diffusion coefficient of the positive electrode material (such as the lithium ion diffusion coefficient) under an infinitesimal excitation current, can avoid (eliminate) the influence of the change in the concentration of ions (such as lithium ions) on the surface of the positive electrode material during the excitation process, and quickly evaluate the structural stability of the positive electrode material.
[0033] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer located on at least one side of the positive electrode current collector, the positive electrode active layer includes a positive electrode material, a conductive agent and a binder, and in the positive electrode active layer, the mass percentage of the positive electrode material is 80% to 95%, the mass percentage of the conductive agent is 1% to 10%, and the mass percentage of the binder is 1% to 10%. Preferably, the positive electrode current collector has only one side surface provided with the positive electrode active layer, and the other side surface is not provided with the positive electrode active layer.
[0034] In a specific implementation, when both sides of the positive electrode collector are provided with positive electrode active layers, the positive electrode active layer on one side is scraped off so that only one side of the positive electrode collector is provided with the positive electrode active layer, and then the positive electrode sheet is assembled into a first battery.
[0035] The positive electrode current collector may include aluminum foil.
[0036] It is understandable that the first battery also includes a negative electrode sheet. In specific implementation, the positive electrode sheet containing the positive electrode material and the negative electrode sheet can be assembled into the first battery.
[0037] Before measuring the diffusion coefficient of the first battery, the first battery may be charged to 4.2-4.25V, then discharged to 18% SOC-20% SOC, and placed at room temperature for 28-30 minutes to stabilize the temperature of the first battery.
[0038] In some embodiments, the negative electrode sheet includes a lithium sheet.
[0039] The first battery may be a button battery (eg, a coin cell).
[0040] Exemplarily, in step (1-2), the state of charge of the first battery can be 10% SOC, 20% SOC, 30% SOC, 40% SOC, 50% SOC, 60% SOC, 70% SOC, 80% SOC, 90% SOC or a range consisting of any two of them.
[0041] In some embodiments, the process of making the charge state of the first battery 10% to 90% SOC to obtain the first battery to be stimulated includes: charging the first battery with constant current and constant voltage at a rate of 0.1C to a charge state of 10% to 90% SOC, with a cut-off current of 0.05C, to obtain the first battery to be stimulated.
[0042] It can be understood that in steps (1-3), in the multiple excitation-resting process, after each excitation, the next excitation is performed after a resting time T; in addition, a K1 is obtained in each excitation-resting process, and multiple K1s are obtained in multiple excitation-resting processes, wherein each K1 corresponds to an excitation current I (i.e., corresponds to an excitation-resting process).
[0043] In multiple excitation-resting processes, the excitation current I during each excitation-resting process can be independently 0.01C to 0.5C, for example, 0.01C, 0.05C, 0.1C, 0.15C, 0.2C, 0.25C, 0.3C, 0.4C, 0.5C or a range consisting of any two of them.
[0044] In any two adjacent excitation-resting processes, the difference in excitation current during excitation can be 0.02C to 0.1C, for example, 0.02C, 0.03C, 0.04C, 0.05C, 0.06C, 0.07C, 0.08C, 0.09C, 0.1C or a range consisting of any two of them.
[0045] In some embodiments, the excitation current used in multiple excitation-rest processes increases sequentially. For example, the first battery to be excited is subjected to five excitation-rest processes using excitation currents of 0.1C, 0.15C, 0.2C, 0.25C, and 0.3C in sequence, and the excitation current used in the five excitation-rest processes increases sequentially.
[0046] The excitation time t (i.e., the pulse current application time) in each excitation-resting process can be 100s to 1200s, such as 100s, 200s, 400s, 600s, 800s, 1000s, 1200s, or a range consisting of any two of them, preferably 600s. It should be noted that the excitation time t of each two excitation-resting processes should be the same.
[0047] The resting time in each excitation-resting process can be 0.5h to 2h, for example, 0.5h, 1h, 1.5h, 2h or any two thereof, preferably 1h. It should be noted that the resting time T in each two excitation-resting processes should be the same.
[0048] In formula 1, ΔEs is the voltage difference before and after the first battery to be stimulated undergoes the xth stimulation-resting process (voltage change caused by the pulse). Specifically, ΔEs=V1-V0, V0 is the voltage of the battery to be stimulated before the xth stimulation-resting process (also the voltage after the x-1th stimulation-resting process), V1 is the voltage of the battery to be stimulated after the xth stimulation-resting process (also the voltage before the x+1th stimulation-resting process); ΔEs is the voltage difference before and after the first battery to be stimulated undergoes the xth stimulation-resting process, which is also the voltage change of constant current charging (discharging).
[0049] In step (1-4), the K1 corresponding to the excitation current I=0 is also the K1 value when infinitesimal current excitation is performed.
[0050] In some embodiments, the first battery to be excited is subjected to five excitation-resting processes using excitation currents I1, I2, I3, I4, and I5 (denoted as x) in sequence, and the corresponding K1, K2, K3, K4, and K5 (denoted as y) are calculated according to formula 1, and x and y are fitted to obtain the relationship equation y=ax between K1 and the excitation current I. 2 +bx+c, wherein c in the above relational equation is the K value when infinitesimal current excitation is performed, that is, K1 corresponding to the excitation current I=0.
[0051] Substitute K1 corresponding to the excitation current I=0 into Formula 2 to calculate the diffusion coefficient D of the positive electrode material.
[0052] In formula 2, V M is the molar volume of the positive electrode material in the positive electrode sheet, which can be calculated by the following formula: V M =F*v / x, where F is Avogadro's constant, v is the unit cell volume of the positive electrode material (which can be obtained by XRD), and x is the number of molecular formulas contained in one unit cell; S is the active contact surface area of the positive electrode material in the positive electrode sheet and the electrolyte of the first battery, which can be calculated according to S=specific surface area of the positive electrode material×the mass of the positive electrode material in the positive electrode sheet.
[0053] The embodiment of the present invention also provides a method for evaluating the structural stability of a positive electrode material, comprising the following steps: (2-1) dividing a positive electrode material into N portions, and making each portion of the positive electrode material into a positive electrode sheet to obtain N positive electrode sheets; wherein N is an integer greater than or equal to 2; (2-2) assembling the N positive electrode sheets into N second batteries; (2-3) cycling y1 second batteries among the N second batteries with the same cycle system to obtain y1 cycled second batteries; wherein the number of cycle i of each two of the y1 second batteries is different; y1 is an integer less than or equal to N; (2-4) cycling the N second batteries with the same cycle system to obtain y1 cycled second batteries; wherein the number of cycle i of each two of the y1 second batteries is different; y1 is an integer less than or equal to N; -4) Perform the following treatments on each of the second batteries after y1 cycles to obtain the diffusion coefficient D of the positive electrode material in each of the second batteries after the cycles, thereby obtaining y1 diffusion coefficients D: (2-41) Disassemble the second battery after the cycles and take out the positive electrode sheet; (2-42) According to the above-mentioned test method for the diffusion coefficient of the positive electrode material, measure the diffusion coefficient D of the positive electrode material in the positive electrode sheet; (2-5) Based on the y1 diffusion coefficients D and their corresponding cycle numbers i, obtain a curve of the diffusion coefficient D changing with the cycle number i; obtain the slope k2 of the change curve, -k2 / 10 -14 <1.2 The structural stability of the positive electrode material is better than -k2 / 10 -14 ≥1.2 corresponds to the structural stability of the positive electrode material.
[0054] According to the inventor's research and analysis: based on the relationship between the diffusion coefficient D (such as lithium ion diffusion performance) of the positive electrode material (positive electrode material to be evaluated) after different cycle numbers i (number of cycles) and the cycle number i, the structural stability (structural anti-destruction performance) of the positive electrode material in the long cycle process can be quickly evaluated. In addition, the real reason for the capacity decay of the positive electrode material in the long cycle process can be distinguished, such as whether the capacity decay is caused by the structural loss (structural collapse) of the positive electrode material or the loss of active ions (such as active lithium), thereby improving the development rate of the positive electrode material, and the evaluation is fast and low-cost.
[0055] Illustratively, in step (2-1), N can be 2, 3, 4, 5, 6, 7, 8, 9, 10 or a range consisting of any two of them.
[0056] In some embodiments, the positive electrode sheet in step (2-1) includes a positive electrode current collector and a positive electrode active layer located on at least one side of the positive electrode current collector, the positive electrode active layer includes the above-mentioned positive electrode material, a conductive agent and a binder, and in the positive electrode active layer, the mass percentage of the positive electrode material is 80% to 95%, the mass percentage of the conductive agent is 1% to 10%, and the mass percentage of the binder is 1% to 10%. Exemplarily, the mass percentage of the above-mentioned positive electrode material is 80%, 85%, 90%, 94.5%, 95% or a range consisting of any two thereof, the mass percentage of the conductive agent is 1%, 2%, 3%, 5%, 8%, 10% or a range consisting of any two thereof, and the mass percentage of the binder is 1%, 2%, 2.5%, 5%, 8%, 10% or a range consisting of any two thereof.
[0057] In some embodiments, the positive electrode material includes a coated LiNi 0.819 Co 0.15 Al 0.03 Y 0.0005 Zr 0.0005 O2. The positive electrode material can be prepared by the following process: a transition metal source (Ni 0.9 Co 0.1 After mixing with lithium source LiOH, Co(OH)2, Al(OH)3, and H2WO4 are added and mixed, and then a second sintering treatment is performed to obtain the positive electrode material (positive electrode active material). The temperature of lithium at the first sintering place can be 700-760°C, such as 700°C, 720°C, 730°C, 750°C, 760°C or a range consisting of any two thereof, and the temperature of the second sintering treatment can be 500-600°C, such as 500°C, 520°C, 550°C, 600°C or a range consisting of any two thereof; water washing can be used in the above washing process.
[0058] The conductive agent in the positive electrode active layer may include superconducting carbon black (conductive agent SP) and / or natural graphite (conductive agent KS-6); the binder may include polyvinylidene fluoride (PVDF).
[0059] The preparation process of the above-mentioned positive electrode sheet may include the following process: mixing the positive electrode material, the conductive agent and the binder in a mass ratio of (80-95): (1-10): (1-10) to obtain a positive electrode active slurry, applying the positive electrode active slurry to at least one side surface of the positive electrode collector, and drying to obtain a positive electrode sheet.
[0060] In step (2-2), the second battery further includes a negative electrode sheet. The embodiment of the present invention does not specifically limit the negative electrode sheet, and a negative electrode sheet commonly used in the art can be selected.
[0061] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer located on at least one side of the negative electrode current collector, wherein the negative electrode active layer includes a negative electrode active material, a thickener, a conductive agent and a binder; wherein, in the negative electrode active layer, the mass percentage of the negative electrode active material is 90% to 96%, the mass percentage of the thickener is 1% to 5%, the mass percentage of the conductive agent is 1% to 2%, and the mass percentage of the binder is 1% to 3%. Exemplarily, the mass percentage of the negative electrode active material is 90%, 91%, 93%, 95%, 96% or a range consisting of any two thereof, the mass percentage of the thickener is 1%, 2%, 3%, 4%, 5% or a range consisting of any two thereof, the mass percentage of the conductive agent is 1%, 1.5%, 2% or a range consisting of any two thereof, and the mass percentage of the binder is 1%, 2%, 3% or a range consisting of any two thereof. When the negative electrode active layer uses the above formula, the negative electrode sheet and the positive electrode sheet can be better matched, which is conducive to improving the accuracy of the evaluation results of the structural stability of the positive electrode material. When preparing the negative electrode sheet, the negative electrode active material, thickener, conductive agent and binder can be dispersed in an appropriate amount of deionized water, and fully stirred and mixed to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector, and after drying, rolling and slitting, the negative electrode sheet is obtained.
[0062] In some embodiments, the negative electrode active material includes graphite.
[0063] The binder may include styrene-butadiene rubber (SBR), the thickener may include carboxymethyl cellulose (CMC), and the conductive agent may include superconducting carbon black (SP).
[0064] The negative electrode current collector may include copper foil.
[0065] In some embodiments, the second battery further comprises an electrolyte, which may be a commonly used electrolyte in the art. Exemplarily, the electrolyte may comprise lithium hexafluorophosphate (LiPF6), ethylene carbonate (EC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC) and fluoroethylene carbonate (FEC), and the content of LiPF6 in the electrolyte is 0.8 to 1.2 M, such as 0.8 M, 1 M, 1.2 M or a range consisting of any two thereof, the volume ratio of EC, EMC and DEC may be (0.8 to 1.2): (0.8 to 1.2): (0.8 to 1.2), such as 1:1:1, 0.8:0.8:1.2, 1.2:0.8:1.2 or a range consisting of any two thereof, and the mass percentage of FEC in the electrolyte may be 1% to 3%, such as 1%, 2%, 3% or a range consisting of any two thereof.
[0066] The present invention does not strictly limit the material selection of the diaphragm, which can be a diaphragm material commonly used in lithium-ion batteries, such as a polypropylene diaphragm (PP), a polyethylene diaphragm (PE), a polypropylene / polyethylene double-layer composite film (PP / PE), a polyimide electrospinning diaphragm (PI), a polypropylene / polyethylene / polypropylene three-layer composite film (PP / PE / PP), a cellulose non-woven fabric diaphragm, or a diaphragm with a ceramic coating.
[0067] The positive electrode sheet, the separator and the negative electrode sheet are wound or stacked to obtain a bare cell (electrode assembly), and the bare cell is packaged in a pre-stamped outer package (such as an aluminum-plastic film bag). After the packaged battery is dried at 85°C in a vacuum, the vacuum degree during the vacuum drying process can be 0.01MPa to 0.1Mpa, preferably 0.085Mpa, and the electrolyte is injected into the dried battery. After the battery is shelved, formed and sealed for the second time, the preparation of the second battery is completed.
[0068] It is understandable that in order to improve the accuracy of the evaluation result, the preparation processes of the N second batteries should be the same.
[0069] In step (2-3), in some embodiments, the cycle regime includes: charging the second battery at a first rate with a constant current to the upper limit of the material voltage, then charging at a constant voltage to a cut-off current of 0.01C to 0.1C, such as 0.01C, 0.05C, 0.1C, or a range consisting of any two thereof, and then discharging the second battery at a second rate to the lower limit of the material voltage; wherein the first rate is 0.5C to 1C, and the second rate is 1C to 3C. Exemplarily, the first rate is 0.5C, 0.7C, 0.9C, 1C, or a range consisting of any two thereof, and the second rate is 1C, 2C, 3C, or a range consisting of any two thereof.
[0070] The upper and lower limits of the voltage of the positive electrode material in the embodiment of the present invention may range from 2.8V to 4.2V.
[0071] In some embodiments, the coated LiNi 0.819 Co 0.15 Al 0.03 Y 0.0005 Zr 0.0005 The upper voltage limit of O2 (positive electrode material) is 4.2V and the lower voltage limit is 2.8V.
[0072] In some embodiments, the number of cycles i of the y1 second batteries is independently 50-1000 cycles (weeks), such as 50 cycles, 100 cycles, 300 cycles, 500 cycles, 800 cycles, 900 cycles, 1000 cycles, or a range consisting of any two thereof. That is, the y1 second batteries are cycled for different numbers of cycles under the same cycle regime to obtain second batteries with different numbers of cycles after y1 cycles.
[0073] Next, the second battery after y1 cycles can be charged to 18% SOC to 22% SOC, for example, 18% SOC, 20% SOC, 22% SOC or any two of them, and then the diffusion coefficient D of the positive electrode material in the second battery after each cycle is obtained according to step (2-4), thereby obtaining y1 diffusion coefficients D. Each cycle number i corresponds to a diffusion coefficient D i , that is, the diffusion coefficient of the positive electrode material in the second battery with cycle number i is recorded as D i .
[0074] In step (2-5), the relationship between the diffusion coefficient D and the cycle number i is obtained based on y1 diffusion coefficients D and their corresponding cycle numbers i, and the structural stability of the positive electrode material is evaluated based on the relationship between the diffusion coefficient D and the cycle number i.
[0075] According to y1 diffusion coefficients D and their corresponding cycle numbers i, a curve of the diffusion coefficient D changing with the cycle number i is obtained; and the slope k2 of the curve is obtained. Specifically, the diffusion coefficient D of the positive electrode material in the second battery with the cycle number i is i As y, the number of cycles i is taken as x, and the fitting equation of the change curve of x and y is y=k2x+b, where k2 is the slope of the change curve.
[0076] According to -k2 / 10 -14 The value of -k2 / 10 -14 <1.2 The structural stability of the positive electrode material is better than -k2 / 10 -14 ≥1.2 corresponds to the structural stability of the positive electrode material. Specifically, -k2 / 10 -14 <1.2 The structural stability of the positive electrode material is excellent, -k2 / 10 -14 <1.2 corresponds to poor structural stability of the positive electrode material.
[0077] In some embodiments, the evaluation method further includes: in step (2-2), the diffusion coefficient D of y2 second batteries among N second batteries is tested according to the above-mentioned test method for the diffusion coefficient of the positive electrode material, and recorded as the initial diffusion coefficient D0 (the initial diffusion coefficient of the charging or discharging process); wherein y2 is an integer, and 1≤y2≤N-y1; evaluating the structural stability of the positive electrode material according to the relationship between the diffusion coefficient D and the number of cycles i also includes: evaluating the structural stability of the positive electrode material according to D0, and the relationship between the diffusion coefficient D and the number of cycles i. That is, D0 can be substituted into the relationship between the diffusion coefficient D and the number of cycles i to check whether the slope K meets the requirements.
[0078] It is understandable that the test conditions of the diffusion coefficients of the y2 second batteries and the diffusion coefficients of the y1 second batteries should be consistent; the initial diffusion coefficient D0 of the y2 second batteries corresponds to the cycle right i=0 (ie x=0 in y=kx+b).
[0079] The present invention is further described below by specific examples and comparative examples. Unless otherwise specified, the reagents, materials and instruments used below are all conventional reagents, conventional materials and conventional instruments, which can be commercially available, and the reagents and materials involved can also be synthesized by conventional synthesis methods.
[0080] Example 1
[0081] Preparation of positive electrode
[0082] The transition metal source (Ni 0.9 Co 0.1 After mixing with lithium source LiOH, 1000 PPM of Co(OH)2, 1000 PPM of Al(OH)3 and 1000 PPM of H2WO4 were added and mixed, and then the positive electrode active material to be evaluated (coated LiNi 0.819 Co 0.15 Al 0.03 Y 0.0005 Zr 0.0005 O2);
[0083] The positive electrode active material to be evaluated, the conductive agent SP, the conductive agent KS-6 and the binder PVDF were mixed in a mass ratio of 94.5:2:1:2.5 to obtain a positive electrode active slurry, and the positive electrode active slurry was coated on both surfaces of the aluminum foil and dried to obtain a positive electrode sheet;
[0084] Preparation of negative electrode
[0085] Graphite, CMC, SP and SBR are mixed in a mass ratio of 95.5:1.5:1:2 to obtain a negative electrode active slurry, the negative electrode active slurry is coated on both surfaces of a copper foil, and after drying, a negative electrode sheet is obtained;
[0086] Preparation of electrolyte
[0087] The electrolyte includes LiPF6, EC, EMC, DEC and FEC, the content of LiPF6 in the electrolyte is 1M, the volume ratio of EC, EMC and DEC is 1:1:1, and the mass percentage of FEC in the electrolyte is 2%;
[0088] The diaphragm is a polypropylene / polyethylene double-layer composite film (PP / PE).
[0089] Preparation of 5 (N=5) second batteries
[0090] The positive electrode sheet, separator and negative electrode sheet are wound or stacked to obtain a bare cell (electrode assembly), and the bare cell is packaged in a pre-stamped outer package (such as an aluminum-plastic film bag). After the packaged battery is dried at 85°C, the electrolyte is injected into the dry battery. After the battery is shelved, formed and sealed for the second time, the preparation of 5 second batteries is completed;
[0091] A second battery is taken for 0.1C cycle to obtain the capacity C0 at 0.1C, specifically including charging the second battery to 4.25V at 0.1C constant current at 25°C, and then charging at constant voltage until the current drops to 0.05C, and discharging the battery to 2.8V at 0.1C constant current after standing for 5 minutes, and recording the first discharge capacity C0 of the battery, then disassembling the second battery, taking out the positive electrode sheet therein, scraping off the positive electrode coating on one side of the positive electrode sheet so that only one side of the positive electrode sheet is retained, and then assembling the positive electrode sheet and the lithium sheet into a button battery, charging the button battery to 4.2V, discharging it to 20% SOC, and placing it at room temperature for 30 minutes, and after the temperature of the button battery is stable, measuring the diffusion coefficient thereof, specifically including: the excitation current is 0.1C, 0.15C, 0.2C, 0.25C, the excitation time t is 600s, the standing time T is 1h, m a (The mass of the positive electrode material in the positive electrode sheet of the button battery) is 0.0028 g; V M (The molar volume of the positive electrode material in the positive electrode sheet in the above button cell) is 20.426 cm 3 ; S (the active contact surface area between the positive electrode material in the positive electrode sheet of the button cell and the electrolyte of the first cell) is 14.336 cm 2 ;M B(the molar mass of the positive electrode material in the above button cell) is 97.36 g / mol; K1 is 0.36, 0.39, 0.348, and 0.265, respectively, and the initial diffusion coefficient D0 is obtained;
[0092] Take 3 (y1=3) second batteries and charge them to 4.2V (upper limit of material voltage) at 1C constant current, then charge them to a cut-off current of 0.05C at constant voltage, then discharge them to 2.8V (lower limit of material voltage) at 2C. After the three second batteries are cycled for 50, 100, and 300 cycles respectively, the three second batteries are charged to 20% SOC to obtain second batteries after three cycles; disassemble the second batteries after three cycles and take out the positive electrode sheets; The positive electrode sheets of the second battery were respectively assembled with lithium sheets into three button batteries (first batteries to be stimulated), and the three button batteries (first batteries) were charged to 4.2V, discharged to 20% SOC (state of charge of the first battery), and placed at room temperature for 30 minutes. After the temperature of the button batteries stabilized, the diffusion coefficients were measured, specifically including: the stimulation current was 0.1C, 0.15C, 0.2C, 0.25C, the stimulation time t was 600s, the standing time T was 1h, m a (The mass of the positive electrode material in the positive electrode sheet of the button battery) is 0.0028 g; V M (The molar volume of the positive electrode material in the positive electrode sheet in the above button cell) is 20.426 cm 3 ; S (the active contact surface area between the positive electrode material in the positive electrode sheet of the button cell and the electrolyte of the first cell) is 14.336 cm 2 ;M B (the molar mass of the positive electrode material in the above button cell) is 97.36 g / mol; the diffusion coefficient D 50 , D 100 , D 300 , after fitting with the number of cycles, the slope of the change curve is obtained as k2, -k2 / 10 -14 The value is 0.3 (less than 1.2), and the structural stability of the surface positive electrode material is good;
[0093] Take a second battery, use the same cycle system as above, obtain a second battery that has been cycled 1000 times, then disassemble it according to the above to obtain its positive electrode sheet, and assemble it into a button battery with a lithium sheet, and then perform 0.1C charge and discharge to obtain 0.1C capacity C1, specifically including charging the second battery that has been cycled 1000 times at 25°C at a constant current of 0.1C to 4.25V, and then charging at a constant voltage until the current drops to 0.05C, and after standing for 5 minutes, discharging the battery at a constant current of 0.1C to 2.8V, recording the discharge capacity C1 of the second battery that has been cycled 1000 times, and comparing C0 and C1 to obtain the capacity loss due to the collapse of the positive electrode material structure as a percentage of 1-R, where R=C1 / C0.
[0094] Example 2
[0095] This embodiment is basically the same as Embodiment 1, except that:
[0096] During the preparation of the positive electrode sheet, the temperature of the first sintering treatment was 715°C, the amount of Co(OH)2 added was 5000PPM, and the temperature of the second sintering treatment was 570°C; the molecular formula of the positive electrode active material to be evaluated was LiNi 0.784 Co 0.18 Al 0.035 Y 0.0005 Zr 0.0005 O2; other conditions remain unchanged.
[0097] in, Figure 2 This is a curve diagram showing the relationship between the excitation current and K1 in the battery after 50 cycles in Example 2.
[0098] Example 3
[0099] This embodiment is basically the same as Embodiment 1, except that:
[0100] During the preparation of the positive electrode sheet, the temperature of the first sintering treatment was 715°C, the amount of Co(OH)2 added was 5000PPM, and the temperature of the second sintering treatment was 600°C; the molecular formula of the positive electrode active material to be evaluated was LiNi 0.781 Co 0.18 Al 0.038 Y 0.0005 Zr 0.0005 O2; other conditions remain unchanged.
[0101] in, Figure 1 is a curve diagram showing the relationship between the excitation current and K1 in the battery before cycling in Example 1; Figure 3 This is a curve diagram showing the relationship between the excitation current and K1 in the battery after 300 cycles in Example 3.
[0102] Example 4
[0103] This embodiment is basically the same as Embodiment 1, except that:
[0104] The state of charge of the first battery is 50% SOC, and other conditions remain unchanged.
[0105] Example 5
[0106] This embodiment is basically the same as Embodiment 1, except that:
[0107] The excitation current I is 0.05C, 0.1C, 0.2C, and 0.3C, and other conditions remain unchanged.
[0108] Example 6
[0109] This embodiment is basically the same as Embodiment 1, except that:
[0110] The state of charge of the first battery is 90% SOC, and other conditions remain unchanged.
[0111] Example 7
[0112] This embodiment is basically the same as Embodiment 4, except that:
[0113] The excitation time t is 100s, the static time is 0.5h, and other conditions remain unchanged.
[0114] Example 8
[0115] This embodiment is basically the same as Embodiment 4, except that:
[0116] The excitation time t is 1200s, the static time is 2h, and other conditions remain unchanged.
[0117] Example 9
[0118] This embodiment is basically the same as embodiment 1, except that NCM111 is selected as the positive electrode active material in this embodiment, and its chemical formula is LiNi 0.31 Co 0.35 Mn 0.34 O2, the voltage upper and lower limits of the positive electrode active material are 2.8-4.4V, and other test conditions are consistent with those in Example 1
[0119] Example 10
[0120] This embodiment is basically the same as the embodiment 1, except that spinel nickel manganese oxide is used as the positive electrode active material, and its chemical formula is LiNi 0.5 Mn 1.5 O4, the voltage upper and lower limits of the positive electrode active material are in the range of 3.8-4.8V, and other test conditions are consistent with those in Example 1.
[0121] Comparative Example 1
[0122] This comparative example uses a conventional method for determining the stability of positive electrode materials in the art, including:
[0123] The second battery of Comparative Example 1 was prepared according to the process of Example 3;
[0124] Take one of the above second batteries and charge it to 4.2V (upper limit of material voltage) at 1C constant current, then charge it to a cut-off current of 0.05C at constant voltage, then discharge it to 2.8V (lower limit of material voltage) at 2C, and perform in-situ XRD analysis on the second battery after cycling it for 1000 times;
[0125] Taking another second battery (uncycled second battery) for in-situ XRD analysis;
[0126] The XRD data of the second battery that was cycled 1000 times and the second battery that was not cycled were refined and the values of the unit cell parameters a and c were calculated. If the c / a value is greater than 4.9, it means that the material maintains a good layered structure, and the larger the c / a value, the more intact the layered structure of the material.
[0127] The test results are shown in the following table. The c / a of the second battery that cycled 1000 times and the second battery that did not cycle were both greater than 4.9, and the c / a after 1000 cycles was slightly greater than that before the cycle, and the difference between the two was only 0.011, indicating that the layered structure was slightly lost after the cycle, but the degree of loss was very low. Since the capacity lost by the collapse of the positive electrode material structure of this comparative example and the capacity lost by the collapse of the positive electrode material structure of Example 3 accounted for 1-R, the sensitivity of the evaluation method of Comparative Example 1 can be evaluated in combination with the test results of the capacity lost by the collapse of the positive electrode material structure in Example 3. Specifically, the capacity lost by the structural collapse of the positive electrode material of Example 3 after 1000 cycles accounted for 1-R (capacity decay) of 31.7%, that is, the capacity lost by the structural collapse of the positive electrode material of Comparative Example 1 after 1000 cycles (capacity decay) is also close to 31.7%, then the c / a of the positive electrode material of Comparative Example 1 after 1000 cycles should be significantly lower than 4.965. From the above analysis, it can be seen that the test method of comparative example 1 has low detection sensitivity for the structural stability of the positive electrode material (the detection sensitivity is not high when the structure of the positive electrode material is slightly lost during the cycle).
[0128]
[0129] Comparative Example 2
[0130] This comparative example adopts the conventional method for detecting the diffusion coefficient of the positive electrode material in the art, including:
[0131] The battery preparation process and the cycle process are consistent with those in Example 3, and the second battery of Comparative Example 2 is prepared. Then, the second battery before the cycle and after 50, 100, and 30 cycles (the cycle system is the same as that in Example 3) is disassembled, the positive electrode sheet is punched out and reassembled with the lithium sheet, and charged to a specified 20% SOC. A single excitation current I is used to perform an excitation-stationary process on the second battery to be excited, the excitation current is 0.1C, and the stationary time is 1h. The diffusion coefficient is calculated according to the following formula 3 using the obtained data:
[0132]
[0133] In formula 3, π is the circumference of a circle; t is the excitation time of each excitation-resting process, in seconds; m a is the mass of the positive electrode material in the positive electrode sheet, in grams; V M is the molar volume of the positive electrode material in the positive electrode sheet, in cm 3 ; S is the active contact surface area between the positive electrode material in the positive electrode sheet and the electrolyte of the first battery, in cm 2 ;M B is the molar mass of the positive electrode active material, in g / mol;
[0134] Then the diffusion coefficient D is fitted with the number of cycles to obtain the slope k2 of the change curve, according to -k2 / 10 -14 The value of is used to evaluate the structural stability of the cathode material;
[0135] Take one second battery of this comparative example and perform 0.1C cycle to obtain the capacity C0 at 0.1C, specifically including charging the second battery to 4.25V at 0.1C constant current at 25°C, then charging at constant voltage until the current drops to 0.05C, standing for 5 minutes, discharging the battery to 2.8V at 0.1C constant current, and recording the first discharge capacity C0 of the battery;
[0136] Take a second battery, use the same cycle system as above, obtain a second battery that has been cycled 1000 times, then disassemble it according to the above to obtain its positive electrode sheet, and assemble it into a button battery with a lithium sheet, and then perform 0.1C charge and discharge to obtain 0.1C capacity C1, specifically including charging the second battery that has been cycled 1000 times at 25°C at a constant current of 0.1C to 4.25V, and then charging at a constant voltage until the current drops to 0.05C, and after standing for 5 minutes, discharging the battery at a constant current of 0.1C to 2.8V, recording the discharge capacity C1 of the second battery that has been cycled 1000 times, and comparing C0 and C1 to obtain the capacity loss due to the collapse of the positive electrode material structure as a percentage of 1-R, where R=C1 / C0.
[0137] Other conditions remain the same as those in Example 3.
[0138] The capacity loss due to the collapse of the positive electrode material structure after 1000 cycles in this comparative example accounts for 32.5% of 1-R (capacity loss rate). However, when a single excitation current is used, the calculation result of the diffusion coefficient D is less accurate, resulting in little difference in the D values for different cycle times. -14 It is 0.09 (the stability of the positive electrode material is good), which contradicts the above results. Therefore, it is impossible to evaluate the structural stability of the positive electrode material by the change of the cyclic diffusion coefficient.
[0139] Referring to Example 1, the diffusion coefficients of the positive electrode materials of Examples 4 to 10 were tested and the structural stability of the positive electrode materials was evaluated. The chemical formula of the positive electrode active material, N, y1, y1, the number of cycles i of the second battery, the state of charge of the first battery, the excitation current I, the excitation time t, the static time, etc. are shown in Table 1. The relationship equations of K1 and the excitation current I corresponding to different excitation currents I, the K1 and y1 diffusion coefficients D and D0 corresponding to the excitation current I = 0, the relationship between the diffusion coefficient D and the number of cycles i, -k2 / 10 -14 , C0, C1, R=C0-C1, etc. are shown in Table 2.
[0140] Table 1
[0141]
[0142]
[0143] Table 2
[0144]
[0145]
[0146] It can be seen that -k2 / 10 of Examples 1 and 2 -14 <1.2, so the positive electrode material structure stability in Examples 1 and 2 is better; and after the second battery of Examples 1 and 2 cycles 1000 times, the capacity loss due to the collapse of the positive electrode material structure (structural loss capacity) R is less than 15%, proving that the positive electrode material has good cycle structure stability, indicating that the evaluation results of the embodiments of the present invention are accurate, while the -k2 / 10 of Example 3 -14>1.2, so the positive electrode material in Example 3 has poor structural stability; and after the battery of this embodiment cycles 1000 times, the capacity lost due to the structural collapse of the positive electrode material accounts for a proportion (structural loss capacity) R higher than 30%, proving that the positive electrode material has poor cyclic structural stability, indicating that the evaluation result of the embodiment of the present invention is accurate; the embodiment of the present invention can accurately calculate the diffusion coefficient (such as the lithium ion diffusion coefficient) of the positive electrode material under an infinitesimal excitation current, and can avoid (eliminate) the influence of the change in the concentration of ions (such as lithium ions) on the surface of the positive electrode material during the excitation process; and can also evaluate the structural stability of the positive electrode material.
[0147] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for testing the diffusion coefficient of a positive electrode material, characterized in that: The following steps are involved: (1-1) Assembling a positive electrode sheet containing a positive electrode material into a first battery; (1-2) setting the state of charge of the first battery to 10% to 90% SOC to obtain a first battery to be stimulated; (1-3) Using different excitation currents I in sequence to perform multiple excitation-resting processes on the first battery to be excited, and obtaining K1 corresponding to different excitation currents I; wherein, during the multiple excitation-resting processes, the K1 corresponding to the nth excitation-resting process is calculated according to the following formula 1: Wherein, ΔEs is the voltage difference between the first battery to be stimulated and the battery after the x-th stimulation-resting process; ΔEt is the voltage difference between the first battery to be stimulated and the battery after the stimulation during the x-th stimulation-resting process; (1-4) obtaining the relationship between K1 and the excitation current I according to K1 corresponding to the different excitation currents I, and obtaining the K1 corresponding to the excitation current I=0 according to the relationship between K1 and the excitation current I; Substitute the K1 corresponding to the excitation current I=0 into Formula 2 to calculate the diffusion coefficient D of the positive electrode material: in, π is the ratio of a circle to a circle; t is the excitation time of the excitation in each excitation-resting process, in seconds; m a is the mass of the positive electrode material in the positive electrode sheet, in grams; V M is the molar volume of the positive electrode material in the positive electrode sheet, in cm 3 ; S is the active contact surface area between the positive electrode material in the positive electrode sheet and the electrolyte of the first battery, in cm 2 ; M B is the molar mass of the positive electrode active material, in g / mol.
2. The method for testing the diffusion coefficient of the positive electrode material according to claim 1, characterized in that: In the multiple excitation-resting processes, the excitation current I during each excitation-resting process is independently 0.01C to 0.5C; and / or, in any two adjacent excitation-resting processes, the difference in the excitation current during the excitation is 0.02C to 0.1C; And / or, the excitation current used in the multiple excitation-resting processes is increased sequentially.
3. The method for testing the diffusion coefficient of the positive electrode material according to claim 1 or 2, characterized in that: The excitation time t of each excitation-resting process is 100s to 1200s; And / or, the resting time in each excitation-resting process is 0.5h to 2h.
4. The method for testing the diffusion coefficient of the positive electrode material according to claim 1 or 2, characterized in that: The process of making the charge state of the first battery 10% to 90% SOC to obtain the first battery to be stimulated includes: charging the first battery with constant current and constant voltage at a rate of 0.1C to the charge state of 10% to 90% SOC to obtain the first battery to be stimulated.
5. The method for testing the diffusion coefficient of the positive electrode material according to claim 1 or 2, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active layer located on at least one side of the positive electrode current collector, wherein the positive electrode active layer comprises the positive electrode material, a conductive agent and a binder, wherein the mass percentage of the positive electrode material in the positive electrode active layer is 80% to 95%, the mass percentage of the conductive agent is 1% to 10%, and the mass percentage of the binder is 1% to 10%; And / or, the first battery further comprises a negative electrode sheet, wherein the negative electrode sheet comprises a lithium sheet; And / or, the first battery is a button battery.
6. A method for evaluating the structural stability of a positive electrode material, characterized in that: The following steps are involved: (2-1) Dividing the positive electrode material into N portions, and making each portion of the positive electrode material into a positive electrode sheet to obtain N positive electrode sheets; wherein N is an integer greater than or equal to 2; (2-2) Assembling the N positive electrode sheets into N second batteries; (2-3) cycling y1 second batteries among the N second batteries using the same cycle regime to obtain second batteries after y1 cycles; wherein the number of cycles i of the cycles of every two of the y1 second batteries is different; and y1 is an integer less than or equal to N; (2-4) Performing the following processing on each of the second batteries after y1 cycles, respectively, to obtain the diffusion coefficient D of the positive electrode material in each of the second batteries after the cycles, thereby obtaining y1 diffusion coefficients D: (2-41) disassembling the second battery after the cycle and removing the positive electrode sheet therefrom; (2-42) According to the method for testing the diffusion coefficient of the positive electrode material according to any one of claims 1 to 5, the diffusion coefficient D of the positive electrode material in the positive electrode sheet is measured; (2-5) According to the y1 diffusion coefficients D and their corresponding cycle numbers i, obtain a variation curve of the diffusion coefficient D with the cycle number i; obtain the slope k2 of the variation curve, -k2 / 10 -14 <1.2 The structural stability of the positive electrode material is better than -k2 / 10 -14 ≥1.2 corresponds to the structural stability of the positive electrode material.
7. The method for evaluating the structural stability of a positive electrode material according to claim 6, characterized in that: The number of cycles i of the cycles of the y1 second batteries is independently 50 to 1000.
8. The method for evaluating the structural stability of a positive electrode material according to claim 6 or 7, characterized in that: The cycle regime includes: charging the second battery at a first rate with a constant current to an upper limit of a material voltage, then charging at a constant voltage to a cutoff current of 0.01C to 0.1C, and then discharging the second battery at a second rate to a lower limit of a material voltage; wherein the first rate is 0.5C to 1C, and the second rate is 1C to 3C.
9. The method for evaluating the structural stability of a positive electrode material according to claim 6 or 7, characterized in that: The evaluation method also includes: in step (2-2), the diffusion coefficient D of y2 of the N second batteries is tested according to the testing method for the diffusion coefficient of the positive electrode material according to any one of claims 1 to 5, and is recorded as the initial diffusion coefficient D0; wherein y2 is an integer, and 1≤y2≤N-y1; the evaluating the structural stability of the positive electrode material according to the relationship between the diffusion coefficient D and the number of cycles i also includes: evaluating the structural stability of the positive electrode material according to D0, and the relationship between the diffusion coefficient D and the number of cycles i.
10. The method for evaluating the structural stability of a positive electrode material according to claim 6, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active layer located on at least one side of the positive electrode current collector, wherein the positive electrode active layer comprises the positive electrode material, a conductive agent and a binder, wherein the mass percentage of the positive electrode material in the positive electrode active layer is 80% to 95%, the mass percentage of the conductive agent is 1% to 10%, and the mass percentage of the binder is 1% to 10%; And / or, the second battery further comprises a negative electrode sheet, the negative electrode sheet comprises a negative electrode current collector, and a negative electrode active layer located on at least one side surface of the negative electrode current collector, the negative electrode active layer comprises a negative electrode active material, a thickener, a conductive agent and a binder; wherein, In the negative electrode active layer, the mass percentage of the negative electrode active material is 90% to 96%, the mass percentage of the thickener is 1% to 5%, the mass percentage of the conductive agent is 1% to 2%, and the mass percentage of the binder is 1% to 3%; And / or, the negative electrode active material includes graphite.